Методы расширения функционально-технологических возможностей машин для измельчения деревьев и кустов - Kovaliok N. S., Ivashnev M. V. (Education environment today: development strategies, 2016)
as part of logging operations performed patent search of technical solutions for fighting forest fires discussed the possibility of using for this purpose the method of throwing soil studies of the processes of creating a multifunctional machine for a flexible technologies technologies.
Keywords: патент; функциональные возможности; технологические возможности; деревья; technology; кусты; измельчение; forest fires; throwing the soil; stewing